Hazardous consequences of textile mill effluents on soil and their remediation approaches - Markandeya; Mohan, Devendra (My University, 2022)
Untreated textile mill effluents are major concern as they associate with various hazardous problems for ecosystems and human health. Complex effluent having a number of dyes, metal contaminations and other organic agents used for softening, printing, heat stabilizing can accumulate in natural sources; soil and water if disposed off without treatment or after in complete treatment. Soil is loose material found on the surface of the earth that importantly offers anchorage for plant, hold water and nutrients. Presence of xenobiotics elements in open and partially covered pits left behind by industrial or domestic activities alter chemical and physical properties of arable soil. This article is mainly focusing the effects of textile mill effluents on soil and their remediation approaches. Bioremediation process is a simple which requires almost negligible energy and very less amount of chemical. This process can be efficiently used in rural areas. This paper gives a review of several researches conducted in the past. © 2022
Keywords: Dye; Health effects; Metal; Soil; Textile mill; Xenobiotics